2016
DOI: 10.1080/13561820.2016.1203296
|View full text |Cite
|
Sign up to set email alerts
|

A network model of communication in an interprofessional team of healthcare professionals: A cross-sectional study of a burn unit

Abstract: Healthcare teams consist of individuals communicating with one another during patient care delivery. Coordination of multiple specialties is critical for patients with complex health conditions, and requires interprofessional and intraprofessional communication. We examined a communication network of 71 health professionals in four professional roles: physician, nurse, health management, and support personnel (dietitian, pharmacist, or social worker), or other health professionals (including physical, respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…With a percentage of 90%, they even computed substantial higher values for interprofessional collaboration compared to our results. The network size of the physicians involved in their study was in line with our results, as a mean of 20 contacts was found (Shoham et al, 2016). Another example is the study of Pomare, Long, Ellis, Churruca, and Braithwaite (2018), in which was shown that the staff of two youth mental health service centers tends to collaborate with colleagues outside of their professional group.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…With a percentage of 90%, they even computed substantial higher values for interprofessional collaboration compared to our results. The network size of the physicians involved in their study was in line with our results, as a mean of 20 contacts was found (Shoham et al, 2016). Another example is the study of Pomare, Long, Ellis, Churruca, and Braithwaite (2018), in which was shown that the staff of two youth mental health service centers tends to collaborate with colleagues outside of their professional group.…”
Section: Discussionsupporting
confidence: 83%
“…Findings in more recent literature meet this need and are consistent with our results. For instance, a recent study discovered that physicians in a team of healthcare professionals of a hospital burn unit were involved in a higher percentage of interprofessional than intraprofessional contacts (Shoham, Harris, Mundt, & McGaghie, 2016). With a percentage of 90%, they even computed substantial higher values for interprofessional collaboration compared to our results.…”
Section: Discussioncontrasting
confidence: 63%
“…13,14 Some studies have shown an inability of some perioperative team members to reflect these attributes consistently. 5,7,15 Multiple studies found communication patterns depend on individual team components, 12,13,16 the perception of psychological safety to raise a concern, 13 and effective structured communication strategies (eg, scripting). 14 Taken together, we found that the published literature shows that perioperative team members require a culture and environment that supports effective and open communication to ensure patient safety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Knowledge about the development of interaction between inter-professional healthcare staff and how it affects the quality of health outcomes, is considered important in cooperation between teams. 5 Earlier studies of radiologists' experiences of interprofessional communication described difficulties such as insufficient information in the referral forms leading to the wrong radiography examination being performed 4,6 Misunderstandings in both inter-personal and inter-professional clinical communication cause suffering in patients and economic losses in the healthcare system. The same researchers 4,6 also described the decreased face-to face communication with patients due to high technology development.…”
Section: Introductionmentioning
confidence: 99%